DETERMINATION OF THE ORIGIN OF REGENERATED FLAX PLANTS IN ANTHER CULTURE - A. I. Soroka; V. A. Lyakh (Вавиловский журнал генетики и селекции)
The possibility to diagnose the ploidy of cells producing regenerated plants in vitro in anther culture has been studied. It is shown by the example of oil flax that population analysis of regenerated plants for segregation on the basis of a marker trait with a simple genetic control can serve as such a method. When microspores are the source of regenerants, segregation of regenerants for a marker that coincides with the segregation at the gamete level is observed. If sporophytic tissues are the source for regenerated plants, there is no segregation. The proposed approach can be applied not only to anther cultures but also to ovule cultures, as well as to any plant species where relevant structures are used to obtain doubled haploids.